Polyurethane foam (PUF) disk passive samplers derived polychlorinated biphenyls (PCBs) concentrations in the ambient air of Bursa-Turkey: Spatial and temporal variations and health risk assessment - Birgül, Aşkın; Kurt Karakuş, Perihan Binnur; Alegria, Henry; Gungormus, Elif; Celik, Halil; Cicek, Tugba (Pergamon-Elsevier Science Ltd, 2017)
Polyurethane foam (PUF) passive samplers were employed to assess air concentrations of polychlorinated biphenyls (PCBs) in background, agricultural, semi-urban, urban and industrial sites in Bursa, Turkey. Samplers were deployed for approximately 2-month periods from February to December 2014 in five sampling campaign. Results showed a clear rural-agricultural-semi-urban-urban-industrial PCBs concentration gradient. Considering all sampling periods, ambient air concentrations of Sigma(43)PCBs ranged from 9.6 to 1240 pg/m(3) at all sites with an average of 24.1 +/- 8.2, 43.8 +/- 24.4, 140 +/- 190, 42.8 +/- 24.6, 160 +/- 280, 84.1 +/- 105, 170 +/- 150 and 280 +/- 540 pg/m(3) for Mount Uludag, Uludag University Campus, Camlica, Bursa Technical University Osmangazi Campus, Hamitler, Agakoy, Kestel Organised Industrial District and Demirtas Organised Industrial District sampling sites, respectively. The ambient air PCB concentrations increased along a gradient from background to industrial areas by a factor of 1.7-11.4.4-Cl PCBs (31.50-81.60%) was the most dominant homologue group at all sampling sites followed by 3-Cl, 7-Cl, 6-Cl and 5-Cl homologue groups. Sampling locations and potential sources grouped in principal component analysis. Results of PCA plots highlighted a large variability of the PCB mixture in air, hence possible related sources, in Bursa area. Calculated inhalation risk levels in this study indicated no serious adverse health effects. This study is one of few efforts to characterize PCB composition in ambient air seasonally and spatially for urban and industrial areas of Turkey by using passive samplers as an alternative sampling method for concurrent monitoring at multiple sites. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Polychlorinated biphenyls (PCBs); Passive air samplers; Background to industrial transect; Health risk assessment; Bursa-Turkey